2021
DOI: 10.1136/bmjgh-2020-004318
|View full text |Cite
|
Sign up to set email alerts
|

“In cities, it’s not far, but it takes long”: comparing estimated and replicated travel times to reach life-saving obstetric care in Lagos, Nigeria

Abstract: BackgroundTravel time to comprehensive emergency obstetric care (CEmOC) facilities in low-resource settings is commonly estimated using modelling approaches. Our objective was to derive and compare estimates of travel time to reach CEmOC in an African megacity using models and web-based platforms against actual replication of travel.MethodsWe extracted data from patient files of all 732 pregnant women who presented in emergency in the four publicly owned tertiary CEmOC facilities in Lagos, Nigeria, between Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 31 publications
2
46
1
Order By: Relevance
“…First, while we have leveraged actual patient data to map the travel paths of the pregnant women, we have not captured the travel time based on their actual ‘experienced’ travel time. However, Google Maps has been shown to be 85% (IQR = 69–98%) accurate in reflecting actual travel time ( Banke-Thomas et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, while we have leveraged actual patient data to map the travel paths of the pregnant women, we have not captured the travel time based on their actual ‘experienced’ travel time. However, Google Maps has been shown to be 85% (IQR = 69–98%) accurate in reflecting actual travel time ( Banke-Thomas et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2016 ). A recent study showed that compared to estimates by GIS-modelled platforms, Google Maps allowed the best-case estimate of reality in an urban LMIC setting ( Banke-Thomas et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study used estimates of distance and travel time from Google Maps, which are closer to reality. 26 However, our study also has some limitations that should be considered in interpreting our findings. First, we used reported clinical data, as such, there are some data that are not routinely recorded in patient notes and others not properly recorded.…”
Section: Bmj Global Healthmentioning
confidence: 82%
“…11 Evidence shows that estimates using Google Maps, like we have done in our study, are more reflective of reality compared with models. 26 On the other hand, self-reported travel time are usually higher than modelled estimates. 11 While, methodological differences may explain the difference, it might also relate with road transport quality.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation